Accelerating effects of biochar for pyrite-catalyzed Fenton-like oxidation of herbicide 2,4-D - Zhu, Xiaoxiao; Li, Jianfa; Xie, Bin; Feng, Dongqing; Li, Yimin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Biochar accelerated 2,4-D degradation using pyrite as the Fenton-like catalyst.•Biochar increased the production of OH in the Fenton-like system.•The mechanism related to the increased production of OH was investigated.•The Fenton-like oxidation of 2,4-dichlorophenol was also accelerated by biochar. Biochar was mixed with natural pyrite to catalyze the Fenton-like oxidation of herbicide 2,4-dichlorophenoxyacetic acid (2,4-D), so as to accelerate the degradation reaction. The accelerating effects of two biochars with different adsorption capacities were compared. The biochar’s functions on accelerating the oxidation were investigated by using radical scavengers, electron spin resonance (ESR), and the chemical probe method. The results indicated that the rate constant (kobs) for the degradation reaction of 2,4-D was enhanced 1.98–2.39 times after the addition of 0.1 g/L of biochar in the pyrite (1.5 g/L) catalyzed system. However, the biochar with the higher adsorption capacity did not outperform the other biochar in accelerating the reaction. Biochar did not influence the Fe lixiviation from pyrite; instead, it accelerated the Fenton oxidation of 2,4-D catalyzed by the dissolved Fe2+. Hydroxyl radicals (OH) were proved to be the major reactive species contributing to the oxidation of 2,4-D, and the addition of biochar increased the cumulative production of OH 2.72 times that in the pyrite-catalyzed system. The mechanism is related to the transformation of O2− to OH by biochar, in which the quinone-like structure acts as the electron shuttle. Based on the identified intermediates and products by gas chromatography-mass spectrometry (GC–MS), high performance liquid chromatography (HPLC), and ion chromatography (IC), as well as the released Cl−, a reaction pathway was summarized for mineralization of 2,4-D. Furthermore, the degradation of 2,4-dichlorophenol (2,4-DCP) was accelerated by biochar as well, indicating the wide feasibility of biochar for accelerating the Fenton-like oxidation of organic pollutants.